1978
DOI: 10.1161/01.res.42.4.550
|View full text |Cite
|
Sign up to set email alerts
|

Effect of positive pressure breathing on lung lymph flow and water content in sheep.

Abstract: SUMMARY We studied the effect of 10 cm H 2 O of continuous positive airway pressure breathing (CPAPB) on steady state lung fluid balance. In 9 of 20 chronically instrumented, unanesthetized sheep, we measured lung lymph flow, pulmonary vascular pressure, cardiac output, pleura! pressure, and lymph and plasma protein concentration during a 2-hour baseline period and 3-4 hours of CPAPB. In eight sheep, we measured the same variables after increasing average left atrial pressure by 18 cm H,O to cause mild interst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

1979
1979
1996
1996

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 36 publications
0
17
0
1
Order By: Relevance
“…However The association of mechanical ventilation and pulmonary edema was made in 1968 (15). It has been repeatedly described in both clinical and animal studies (16)(17)(18)(19). Webb and Tierney (19) have found that alveolar and perivascular edema resulted from ventilation with high inspiratory pressures at low end-expiratory volumes.…”
Section: Resultsmentioning
confidence: 99%
“…However The association of mechanical ventilation and pulmonary edema was made in 1968 (15). It has been repeatedly described in both clinical and animal studies (16)(17)(18)(19). Webb and Tierney (19) have found that alveolar and perivascular edema resulted from ventilation with high inspiratory pressures at low end-expiratory volumes.…”
Section: Resultsmentioning
confidence: 99%
“…Since, through most of our experiment, the entire lung was in zone III (West et al, 1964), the assumptions used in calculating pulmonary microvascular pressure are more likely valid than under normal hemodynamic conditions. Second, we assumed that interstitial hydrostatic pressure equalled alveolar pressure (Woolverton et al, 1978). It is certainly likely that as the fluid filtration rate increased, perimicrovascular pressure increased (Taylor et al, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…It is certainly likely that as the fluid filtration rate increased, perimicrovascular pressure increased (Taylor et al, 1973). This local increase in interstitial pressure would aid fluid flux through the interstitial space resulting in formation of perivascular and peribronchial fluid cuffs (Staub, 1978). The extent to which fluid flux through the interstitium may modulate changes in interstitial pressure around exchanging vessels during formation of pulmonary edema is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the use of PEEP is limited in certain cases of ARDS. During ventilation with PEEP the transvascular flux of lung water has been found either to be increased (8) or to be unchanged (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%